Clinical performance of the Nevisense system in cutaneous melanoma detection: an international, multicentre, prospective and blinded clinical trial on efficacy and safety. (1st November 2014) - Malvehy, J.; Hauschild, A.; Curiel‐Lewandrowski, C.; Mohr, P.; Hofmann‐Wellenhof, R.; Motley, R.; Berking, C.; Grossman, D.; Paoli, J.; Loquai, C.; Olah, J.; Reinhold, U.; et al.
Summary: Background: Even though progress has been made, the detection of melanoma still poses a challenge. In light of this situation, the Nevisense electrical impedance spectroscopy (EIS) system (SciBase AB, Stockholm, Sweden) was designed and shown to have the potential to be used as an adjunct diagnostic tool for melanoma detection. Objectives: To assess the effectiveness and safety of the Nevisense system in the distinction of benign lesions of the skin from melanoma with electrical impedance spectroscopy. Methods: This multicentre, prospective, and blinded clinical study was conducted at five American and 17 European investigational sites. All eligible skin lesions in the study were examined with the EIS‐based Nevisense system, photographed, removed by excisional biopsy and subjected to histopathological evaluation. A postprocedure clinical follow‐up was conducted at 7 ± 3 days from the initial measurement. A total of 1951 patients with 2416 lesions were enrolled into the study; 1943 lesions were eligible and evaluable for the primary efficacy end point, including 265 melanomas – 112 in situ and 153 invasive melanomas with a median Breslow thickness of 0·57 mm [48 basal cell carcinomas (BCCs) and seven squamous cell carcinomas (SCCs)]. Results: The observed sensitivity of Nevisense was 96·6% (256 of 265 melanomas) with an exact one‐sided 95% lower confidence bound estimated at 94·2% and an observed specificity of 34·4%, and an exact two‐sided 95% confidence bound estimated at 32·0–36·9%. The positive and negative predictive values of Nevisense were 21·1% and 98·2%, respectively. The observed sensitivity for nonmelanoma skin cancer was 100% (55 of 48 BCCs and seven SCCs) with an exact two‐sided 95% confidence bound estimated at 93·5–100·0%. Conclusions: Nevisense is an accurate and safe device to support clinicians in the detection of cutaneous melanoma.